2021
DOI: 10.1017/s1368980021002603
|View full text |Cite
|
Sign up to set email alerts
|

Examining recent trends in the racial disparity gap in tap water consumption: NHANES 2011–2018

Abstract: Objective As tap water distrust has grown in the US with greater levels among Black and Hispanic households, we aimed to examine recent trends in not drinking tap water including the period covering the US Flint Water Crisis and racial/ethnic disparities in these trends. Design Cross-sectional analysis. We used log-binomial regressions and marginal predicted probabilities examined US nationally-representative trends in tap and bottled water consumption overall and by race/ethnicity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…While mothers' perceptions of their home tap water did not vary by race, ethnicity or educational attainment, differences were observed in mothers' perceptions of tap water in general by these sociodemographic characteristics. National and community-specific studies have documented that Black, Hispanic/Latinx and low socioeconomic status individuals are more likely than White and high socio-economic status individuals to report that tap water is not safe to drink (8,9,17,27,28) and are less likely to consume tap water (14,15) . Further, Black and Hispanic/ Latinx adults in the USA are twice as likely as White adults to consume bottled water (29,30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mothers' perceptions of their home tap water did not vary by race, ethnicity or educational attainment, differences were observed in mothers' perceptions of tap water in general by these sociodemographic characteristics. National and community-specific studies have documented that Black, Hispanic/Latinx and low socioeconomic status individuals are more likely than White and high socio-economic status individuals to report that tap water is not safe to drink (8,9,17,27,28) and are less likely to consume tap water (14,15) . Further, Black and Hispanic/ Latinx adults in the USA are twice as likely as White adults to consume bottled water (29,30) .…”
Section: Discussionmentioning
confidence: 99%
“…In total, media reports suggest that distrust of tap water and distrust of government officials to keep tap water safe are high among Michigan residents (13) . Nationally, the percentage of adults and children drinking tap water has decreased dramatically since the Flint Water Crisis, particularly among individuals of colour (14) . Further, while avoidance of tap water had been decreasing among US children prior to the Flint Water Crisis, more children, specifically Black and Hispanic children, report avoiding tap water after the Flint Water Crisis (15) .…”
mentioning
confidence: 99%
“…These ndings are important because human behavior and health decision-making are largely driven by experiences, perceptions, and attitudes 3,20 . Individuals who perceive their water to be dangerous or of suboptimal quality are more likely to avoid or not pay for piped water 26,27 , consume bottled water 28,29 , and substitute sugar-sweetened beverages for water 23,30 , which in turn have negative consequences for the sustainability of water services as well as human and environmental well-being. Bottled water production, for instance, is a resource-intensive process that generates considerable greenhouse gas emissions and other contaminants that can pollute local water sources; it is also vastly more expensive than tap water and often of poorer quality [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The Murmansk region is one of the most urbanized regions of Russia; the population as of 1 January 2021, was 732,000 people. The largest cities in the region are Murmansk (282,851), Apatity (53,847), Monchegorsk (40,675), Kandalaksha (29,750), Kirovsk (25,944), and Olenegorsk (19,887) [39]. In this study, the elemental composition in the water of the most popular springs near or within the territory of large cities in the region was studied (Figure 1).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Back in 2010, the journal Nature showed that almost 80% of the world's population is threatened by water pollution [38]. There is a growing distrust of tap water, so people in cities increasingly choose bottled or spring water for drinking [17,39].…”
Section: Camentioning
confidence: 99%